Recent progress in the development of carbon quantum dots for cell imaging. Issue 1 (20th January 2021) - Guo, Huazhang; Wang, Liang
Abstract: Carbon quantum dots (CQDs) have attracted widespread attention due to the significant advantages in optical and environmentally friendly performance. Herein, we focused on the development of CQDs synthesized by advanced molecular fusion technology. Meanwhile, the applications of CQDs on various target cell imaging were also demonstrated. Our summary looks back to the feasible preparation strategy of CQDs and forward into their potent applications in early diagnosis and treatment of cancer in the future.